Pelatihan Aplikasi Pengolah Data Untuk Staf Pemerintah Desa Baturiti - Utama, I Putu Kussa Laksana; Kartika, Luh Gede Surya; Saskara, I Putu Adi; Pratama, Putu Adi; Bayu Praditya; Riska Mahardika; Sanjaya, I Gede Wahyu (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
The very rapid development of technology should make it easier to provide services to the community. Baturiti Village, Tabanan Regency, for example, the use of technology is now evenly used by all village officials. However, the use of the most basic technology is still inadequate, this can be seen from the way data is processed in terms of using the Microsoft Excel application. Village officials' methods of tidying up tables, grouping data, sorting data and printing work areas still often experience problems. This will certainly have an impact on service times to the community. Based on these problems, it was felt that the service team needed to provide service in the field of information technology, especially training on the use of data processing applications for Baturiti village officials. This service program is aimed at providing additional insight into technological developments, especially regarding the procedures for using data processing applications for Baturiti Village equipment, so that in the future the knowledge gained can help in optimizing services to the community. To test the success of this activity, it was carried out using a Post Test and distributing questionnaires. The results achieved from this activity were that this activity could be completed well, as seen from the enthusiasm of the activity participants. Apart from that, the post test results obtained from 22 training participants obtained an average result of 0.87 which is included in the Very Good category. Apart from the post test results, to obtain improvements for subsequent activities, the implementing team distributed questionnaires which were used to measure the success of this training, where the results of respondents showed very good scores.